Operation and management of a community treatment center using telemedicine for foreign patients with mild COVID-19 symptoms. Issue 47 (24th November 2021) - Kim, Han Bit; Han, Sangsoo; Shin, Heejun; Lee, Young Hwan; Lee, Kyung Min; Kwak, Jae Ryoung; Cho, Young Soon; Kim, Hojung; Lim, Hoon; Kim, Gi Woon; Eo, Eunkyung; Noh, Hyun
Abstract : Abstract: South Korean studies on coronavirus disease-2019 (COVID-19) treatment have described the use of community treatment centers (CTCs), which combine elements of the home and hospital, to isolate and treat mild COVID-19 patients. While the number of South Koreans diagnosed with COVID-19 cases has varied greatly by season, the number of confirmed cases in foreign nationals has shown no seasonality, with an average of around 25 to 30 per day. For foreign patients, accommodation arrangements and travel routes may be difficult; they may also have difficulty accessing medical care, so require careful management. We discuss our experience in operating and managing a CTC for foreign COVID-19 patients arriving in South Korea with mild symptoms. We also propose guidelines for efficient use of resources with respect to treating these patients in CTCs. We present the clinical findings of patients treated at the CTC between 7 October and 22 November 2020, and make some recommendations. We quarantined and treated foreign patients with mild symptoms of COVID-19 at the Ansan CTC. Discharge is determined based on clinical symptoms rather than polymerase chain reaction results. Medical and administrative staff use building A, while building B is used for isolating patients. Medical rounds are in the form of twice-daily video calls. Three kinds of foods with medication are served according to the patient's country of origin. In total, 315 patients were admitted to the Ansan CTC between 7 October and 22 November 2020; 145 of them were discharged from the CTC and 26 were transferred to other hospitals. To utilize medical resources efficiently during the pandemic, it is desirable to reserve CTCs exclusively for foreign patients. Abstract : Supplemental Digital Content is available in the text